Rapid and effective fusion repair of severed digital nerves using neurorrhaphy and bioengineered solutions including polyethylene glycol: A case report - Lopez, Stephen; Bittner, George D.; Treviño, Richard C. (Frontiers in Cellular Neuroscience, 2023)
Peripheral nerve injuries (PNIs) that consist of simple nerve severance often result in severe motor impairment and permanent loss of function. Such patients face significant costs and pose major burdens to healthcare systems. Currently, the most promising surgical technique to achieve the best clinical outcome after such PNIs is immediate primary coaptation of severed nerve ends by microsutures (neurorrhaphy). However, recovery is often poor and delayed for many months due to Wallerian degeneration (WD) and slow (1–2 mm/day) axonal outgrowths from severed proximal axons that may not properly reinnervate denervated afferent/efferent targets that have atrophied. In contrast, recent pre-clinical studies using polyethylene glycol (PEG) to facilitate primary nerve repair have greatly improved the rate and extent of sensory and motor recovery and prevented much WD and muscle atrophy. That is, PEG-fused axons rapidly establish proximal–distal axoplasmic/axolemmal continuity, which do not undergo WD and maintain the structure and function of neuromuscular junction (NMJ). PEG-fused axons rapidly reinnervate denervated NMJs, thereby preventing muscle atrophy associated with monthslong denervation due to slowly regenerating axonal outgrowths. We now describe PEG-mediated fusion repair of a digital nerve in each of two patients presenting with a digital laceration resulting in total loss of sensation. The first patient’s tactile perception improved markedly at 3 days postoperatively (PO). Two-point discrimination improved from greater than 10 mm at initial presentation to 4 mm at 11-week PO, and the Semmes–Weinstein monofilament score improved from greater than 6.65 to 2.83 mm, a near-normal level. The second patient had severe PO edema and scar development requiring a hand compression glove and scar massage, which began improving at 11-week PO. The sensory function then improved for 4 months PO, with both two-point discrimination and Semmes–Weinstein scores approaching near-normal levels at the final follow-up. These case study data are consistent with data from animal models. All these data suggest that PEG-fusion technologies could produce a paradigm shift from the current clinical practice of waiting days to months to repair ablation PNIs with autografts, anucleated nerve allografts, or conduits in which the patient outcome is solely dependent upon axon regeneration over months or years.